Thermochemical energy storage performances of Ca-based natural and waste materials under high pressure during CaO/CaCO3 cycles. (1st October 2019) - Sun, Hao; Li, Yingjie; Bian, Zhiguo; Yan, Xianyao; Wang, Zeyan; Liu, Wenqiang
Highlights: Limestone carbonated at high pressure shows high energy storage capacity. Carbide slag carbonated at high pressure has stable energy storage capacity. High carbonation pressure retards sintering and pore-plugging of CaO. CaO grains carbonated at high pressure grow slowly with number of cycles. Ca-based materials carbonated at high pressure possess porous structure. Abstract: Thermochemical energy storage based on CaO/CaCO3 cycles is a promising technique used in concentrated solar power plant. The high global efficiency can be achieved under high carbonation pressure and temperature. In this work, limestone and carbide slag were chosen as the representatives of Ca-based natural and waste materials, respectively. The thermochemical energy storage performances of the limestone and the carbide slag under high carbonation pressure condition (>1.0 MPa) during CaO/CaCO3 cycles were studied in a pressurized dual fixed-bed reactor. The effects of carbonation temperature, calcination temperature and number of energy storage cycles under high carbonation pressure condition were also researched. The energy storage capacities of two Ca-based materials are enhanced significantly with increasing the carbonation pressure. The carbonation conversion and energy density of the limestone carbonated under 1.3 MPa are about 0.83 and 2626 kJ/kg after 10 cycles, respectively, which are 1.76 times as high as those carbonated under 0.1 MPa. The carbide slag carbonated under high pressure exhibits higher cyclic stability than the limestone during long-term energy storage cycles. In addition, the optimum temperatures for the energy storage of the limestone and the carbide slag carbonated under 1.3 MPa are 850–900 °C and 800–850 °C, respectively. High carbonation pressure can mitigate the sintering and pore-plugging of CaO. The average grain size of CaO carbonated under higher pressure increases more slowly with the number of energy storage cycles. The microstructure of the Ca-based material carbonated under high pressure appears more porous than that carbonated under atmospheric pressure. Increasing carbonation pressure is an effective method to improve the energy storage capacity of Ca-based material. The carbide slag is also a good candidate for long-term thermochemical energy storage under high pressure.